A study of inflation in China - Hu, Xiaoli (2012)
This paper seeks to find the determinants of inflation in China from both a qualitative and quantitative perspective during the period 2000-2011. In the qualitative analysis, we employ the aggregate demand/aggregate supply (AD/AS) framework to construct a mixed inflation model which postulates that the potential determinants of inflation in China are money supply or bank loans, real Gross Domestic Product (GDP), real effective exchange rate, international commodity prices, average nominal wages and inflationary expectations. In the quantitative analysis, with the autoregressive distributed lag (ARDL) framework, we first identify the long run determinants of inflation, and then an error correction model (ECM) is employed to estimate the short run dynamics. We remark that in the long run, the primary source of inflation in China is growth of money supply or bank loans. In the short run, we conclude that while both growth of money supply or bank loans and inflationary expectations influence China’s inflation, inflationary expectations play a more important role.